2004
DOI: 10.1385/abab:117:3:175
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of B-Subunit of <I>Escherichia coli</I> Heat-Labile Enterotoxin in Tobacco by Optimization of Coding Sequence

Abstract: Escherichia coli heat-labile toxin (LT) is a potent mucosal immunogen and immunoadjuvant for coadministered antigens. We synthesized a gene encoding the B-subunit of LT (LTB) adapted to the coding sequence of tobacco plants and fused to the endoplasmic reticulum retention signal SEKDEL to enhance its level of expression in plants. The synthetic LTB gene was cloned into a plant expression vector adjacent to the CaMV 35S promoter and was introduced into tobacco by Agrobacterium-mediated transformation. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 26 publications
2
25
0
1
Order By: Relevance
“…This increases the translational efficiency and subsequently improves the recombinant protein expression and the overall costs of protein production in the considered host [60,61]. Codon optimization is employed to increase the production of human and animal recombinant proteins in the tobacco expression system [49,57].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the translational efficiency and subsequently improves the recombinant protein expression and the overall costs of protein production in the considered host [60,61]. Codon optimization is employed to increase the production of human and animal recombinant proteins in the tobacco expression system [49,57].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…In this regard and because of the mammalian origin of LFchimera, genetic codes for 20 out of the 34 amino acids of the LFchimera peptide sequence were codonoptimized for expression in tobacco whole plant, and the translational start-site of the heterologous peptide was modified to match the Kozak consensus for efficient initiation of translation in plants (Figure 1) [61,63]. The results from RT-PCR showed that the LFchimera was properly transcribed, and the transcripts were stable in the plants.…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%
“…After blocking, the filter was incubated with either anti-LTB antiserum (Immunology Consultants Laboratory, Inc.) or anti-ApxIIA antiserum (26) then was bound to anti-rabbit IgG or anti-mouse IgG, respectively, conjugated to alkaline phosphatase as a secondary antibody (Promega). The color was developed using 5-bromo-4-chloro-3-indolylphosphate-nitroblue tetrazolium (BCIP-NBT) (USB) in TMN buffer (100 mM Tris [pH 9.5], 5 mM MgCl 2 , and 100 mM NaCl), according to the methods described by Kang et al (22).…”
Section: Vector Constructionmentioning
confidence: 99%
“…The plate was read at 405 nm in an ELISA reader (Packard Instrument MRA-006) and quantified via comparison with a known quantity of purified bacterial LTB. The purified bacterial LTB, obtained from the previous study (22), was serially diluted within the range of the concentrations from 0.1 ng to 10 ng. GM1 ganglioside binding assay.…”
Section: Elisa Quantification Of Recombinant Ltb Proteinmentioning
confidence: 99%
“…planta-pharma, plant bioreactors, plant biofactory, 그리고 pharmaceutical gardening 등 많은 용어들이 비슷한 의미로 혼용하여 사용하고 있다 (Basaran and Rodriguez-Cerezo 2008 (Mason et al 1998;Kang et al 2004), 유전자의 안정성에 영향을 미 치는 요소 제거 (De Jaeger et al 2002;Ibrahim et al 2001;Outchkourov et al 2003) (Barta et al 1986;De Zoeten et al 1989;Sijmons et al 1990), 1989년에는 담배의 잎에서 항체를 발현을 시킴으로서 식물에서 복잡 한 형태의 치료용 동물단백질을 생산할 수 있다는 가능성 이 제시되었다 (Hiatt et al 1989 (Poirier et al 1992).…”
unclassified